Isolation of Macromolecular Polymeric Ingredients from Waste Biomass Materials and their Characterization. (2016) - Bilgic, Ezgi; Yaman, Serdar; Haykiri-Acma, Hanzade
Abstract: The macromolecular polymeric ingredients of biomass were isolated from waste biomass species such as sunflower seed shell and hazelnut shell. For this purpose, these biomass samples were treated in sequential extraction procedures using chemical reagents, and the individual polymers such as lignin and holocellulose were isolated and characterized. The chemical and thermal properties of isolated ingredients were compared with the parent materials considering SEM micrographs, thermal analysis curves (TGA and DTA) and surface functionalities.